ETHNOBIOLOGICAL STUDY OF CHINGKUI, TRADITIONAL FOOD FROM LAMNO, ACEH JAYA, INDONESIA - Ardhana Yulisma; Nir Fathiya; Astho barni (Universitas Ubudiyah Indonesia, 2026)
This study entitled Ethnobiological Study of Chingkui, Traditional Food from Lamno, Aceh Jaya, Indonesia aimed to document the ethnobiological dimensions of chingkui, focusing on plant diversity, cultural significance, and knowledge transmission. A qualitative ethnobiological approach was employed through semi-structured interviews, participant observation, and ethnobotanical documentation involving 60 informants from three villages in Lamno. The study identified 13 plant species from 13 families used in chingkui preparation, each possessing culinary, medicinal, and symbolic functions. Findings revealed that chingkui represents a biocultural heritage integrating ecological knowledge, spirituality, and communal identity, with women playing a central role in preserving traditional knowledge.